2002
DOI: 10.1097/00000539-200209000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Magnesium Prolongs Fentanyl Analgesia: A Prospective, Randomized, Controlled Trial

Abstract: Magnesium occurs naturally in the spinal cord and blocks the NMDA glutamate channel. In animal studies, intrathecal magnesium sulfate improves spinal morphine analgesia. For patients receiving spinal analgesia for labor, the addition of magnesium sulfate to the opioid fentanyl prolonged analgesia with no increase of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
92
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 20 publications
9
92
3
Order By: Relevance
“…Consistent with published results [3,7], we found that the mean duration of spinal anesthesia was prolonged with the addition of IT MgSO 4 , but this difference was not statistically significant. The absence of a statistically significant difference may simply indicate that IT MgSO 4 actually does not prolong the duration of spinal anesthesia, or it may be due to the limited statistical power of the study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with published results [3,7], we found that the mean duration of spinal anesthesia was prolonged with the addition of IT MgSO 4 , but this difference was not statistically significant. The absence of a statistically significant difference may simply indicate that IT MgSO 4 actually does not prolong the duration of spinal anesthesia, or it may be due to the limited statistical power of the study.…”
Section: Discussionsupporting
confidence: 90%
“…Similar reductions in analgesic requirements have been reported in other orthopedic and non-orthopedic populations [7,9,12,15,16]. This effect is in contrast to that reported in a number of other studies [3,8]. Taken together, these results seem to indicate that in order for total analgesic consumption to be reduced, higher doses of MgSO 4 are required, similar to the dose used in our study (100 mg) and that of Arcioni et al [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was demonstrated that the ineffectiveness of magnesium in intravenous applications may be due to its inability to form effective cerebrospinal fluid concentrations because of inadequate penetration through the blood-brain barrier [13]. For this object, Buvanendran et al [20] used magnesium intrathecally and demonstrated that 50 mg intrathecal use of magnesium prolonged analgesia in adults. In the light of these data, we thought that we could get the same effect through epidural caudal use of magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, we used magnesium epidurally and did not detect any neurological deficit in the patients in the postoperative period. Buvanendran et al in the first randomized clinical study in literature, took as a reference 188 lg of intrathecal magnesium potentializing morphine antinociception for postoperative pain by taking a rat model that they used in their previous study [20,21]. The differences between rats and humans in cerebral fluid amount and body weight were taken into account.…”
Section: Discussionmentioning
confidence: 99%